2018
DOI: 10.1007/s41669-018-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Strimvelis® for Treating Severe Combined Immunodeficiency Caused by Adenosine Deaminase Deficiency: An Evidence Review Group Perspective of a NICE Highly Specialised Technology Evaluation

Abstract: The Centre for Reviews and Dissemination and Centre for Health Economics Technology Assessment Group at the University of York was commissioned by the National Institute for Health and Care Excellence (NICE) Highly Specialised Technologies (HST) programme to act as the independent Evidence Review Group (ERG) for an appraisal of Strimvelis ® , a gene therapy treatment for adenosine deaminase deficiency–severe combined immunodeficiency (ADA-SCID). This paper describes the manufacturing com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The cost effectiveness of Strimvelis was examined in 2 analyses, of which 1 was deemed to be cost effective. South et al (2018) 32 reported a NICE Highly Specialised Technology Evaluation which estimated the most plausible ICERs for Strimvelis to be lower than £100 000 per QALY gained. NICE approved Strimvelis for the treatment of adenosine deaminase severe combined immunodeficiency, where a matched related donor is unavailable 31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cost effectiveness of Strimvelis was examined in 2 analyses, of which 1 was deemed to be cost effective. South et al (2018) 32 reported a NICE Highly Specialised Technology Evaluation which estimated the most plausible ICERs for Strimvelis to be lower than £100 000 per QALY gained. NICE approved Strimvelis for the treatment of adenosine deaminase severe combined immunodeficiency, where a matched related donor is unavailable 31 .…”
Section: Resultsmentioning
confidence: 99%
“…However, many were incomplete with respect to important methodological detail. The perspective was unclear in 7 of the studies 15,16,24,26,28,31,32 . Two studies 15,16 did not state explicitly the modelling approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD34 + cells are then transduced with a gammaretrovirus vector carrying the gene for human adenosine deaminase (ADA), then reinfused into the patient. These cells home to the patient’s bone marrow where CD34 + cells replicate and generate normal ADA protein to correct the deficiency ( South et al, 2018 ). Zyntelgo was approved in Europe in 2019 for the treatment of beta-thalassemia.…”
Section: Dna Therapeuticsmentioning
confidence: 99%
“…Among 6000 phenotypes of genetic disorders with known molecular basis that have been identified to date, the hematological diseases became the first successful cases for the development of gene therapy products. Thus, Strimvelis was approved by EMA in 2016 for clinical use in children with adenosine deaminase deficiency [139]. With the invention of robust genome-editing tools, this approach became more and more attractive.…”
Section: Inherited Diseasesmentioning
confidence: 99%